2021
DOI: 10.1093/ajcn/nqaa362
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity is associated with magnetic resonance–determined nonalcoholic fatty liver and liver fibrosis in low-income, middle-aged adults with and without HIV

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is the most prevalent liver disease in the United States. Food-insecure individuals often depend on low-cost, energy-dense but nutritionally poor foods, resulting in obesity and chronic diseases related to NAFLD. Objectives To determine whether food insecurity is associated with NAFLD in a cohort of HIV and hepatitis C virus (HCV) infected and uninfected adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
4
19
0
Order By: Relevance
“…Food insecurity in high‐income settings tends to result in becoming overweight or experiencing obesity; however, PLWH who are food insecure may experience issues of both underweight and overweight (Sirotin et al., 2012, 2014; Tamargo et al., 2021). Weight issues were often tied to the inability of food banks to provide nutritious food, and existing research suggests WLWH experience issues with weight maintenance as a result of food insecurity (Eicher‐Miller, 2020; Sirotin et al., 2014; Weiser, Fernandes, et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity in high‐income settings tends to result in becoming overweight or experiencing obesity; however, PLWH who are food insecure may experience issues of both underweight and overweight (Sirotin et al., 2012, 2014; Tamargo et al., 2021). Weight issues were often tied to the inability of food banks to provide nutritious food, and existing research suggests WLWH experience issues with weight maintenance as a result of food insecurity (Eicher‐Miller, 2020; Sirotin et al., 2014; Weiser, Fernandes, et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…According to our result, almost 60% of PCOS women and 30% of non-PCOS women had FI. Around the world, FI is one of the most challenging conditions, especially in women, occurs as a consequence of nonsufficient or restricted availability of safe food resources, which can exert several adverse effects, such as obesity [ 30 , 31 , 54 56 ] and reduced physical activity [ 57 ]. Furthermore, obesity itself which can be manifested as high waist circumference can amplify the severity of metabolic disorders, such as PCOS [ 58 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, food insecurity (FI) is considered as a condition that there is limited or uncertain access to adequate healthy diets, which can cause a broad spectrum of socio-emotional issues, obesity, and chronic disorders [ 30 , 31 ] that may be affected by several socio-economic factors [ 32 ]. It was found that FI itself can contribute to the disturbance of the eating patterns and thereby the dietary intakes [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our result, almost 60% of women with PCOS and 30% of non-PCOS women had FI. Around the world, FI especially in women is one of the most challenging can exert several adverse effects such as obesity [30,31,[53][54][55] and altering physical activity [56]. Furthermore, obesity itself which can be manifested as high waist circumference can amplify the severity of kinds of metabolic disorders such as PCOS [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, food insecurity (FI) is considered as a condition that there is limited access to an adequate healthy diet which can cause a wide spectrum of socio-emotional issues, obesity, and chronic disorders [30,31] that may be affected by several socio-economic factors [32]. Nowadays, almost 795 million persons suffer from FI around the world [33].…”
Section: Introductionmentioning
confidence: 99%